Anti-interleukin-5/anti-interleukin-5 receptor α treatment improves self-reported work productivity in patients with severe eosinophilic asthma: a prospective cohort trial - Lina Brinkmann; Jan Fuge; Tobias Welte; Hendrik Suhling; Nora Drick (ERJ Open Research)
Background Severe asthma affects the working life of millions of people worldwide. Interleukin (IL)-5/anti-interleukin-5 receptor α (IL-5Rα) antibodies are highly effective in reducing symptoms in patients with severe eosinophilic asthma. We analysed effects of anti-IL-5/anti-IL-5Rα treatment on self-reported productivity and absenteeism at work in patients with severe eosinophilic asthma. Methods In this prospective single-centre study, patients with severe eosinophilic asthma received a questionnaire assessing their actual occupational status and the influence asthma has on their work life, productivity and missed days at work prior to initiation of antibody treatment and after 6 and 12 months of therapy. Among others, the Work Productivity and Activity Impairment Questionnaire: Specific Health Problem (WPAI:SHP) was used. Results Out of 54 patients with a median age of 60 years, 27 (50%) were employed. In addition to an increase in asthma control and lung function, self-reported productivity increased significantly with a decrease on the WPAI:SHP from 30% (interquartile range (IQR) 20–50%) to 10% (IQR 0–27.5%) under treatment (p=0.001). Furthermore, self-reported missed days at work were reduced from 2 days·month−1 (IQR 1.75–6 days·month−1) to 0 days·month−1 (IQR 0–2 days·month−1; p=0.067). At baseline 22 employed patients (81%) stated they were affected at work by their asthma. After 12 months of treatment, this number decreased to eight patients (30%; p=0.038). Conclusions This prospective analysis could prove the substantial impact severe asthma has on patients’ working life. Anti-IL-5/anti-IL-5Rα treatment in patients with severe eosinophilic asthma leads to a significant increase in self-reported productivity at work, and after 12 months of treatment patients state substantially fewer negative effects on their working situation.